Faking revisited: Exerting strategic control over performance on the Implicit Relational Assessment Procedure. (1st July 2016) - Hughes, Sean; Hussey, Ian; Corrigan, Bethany; Jolie, Katie; Murphy, Carol; Barnes‐Holmes, Dermot
Abstract: Across four studies, we demonstrate that effects obtained from the Implicit Relational Assessment Procedure, like those obtained from other indirect procedures, are not impervious to strategic manipulation. In experiment 1, we found that merely informing participants to "fake" their performance without providing a concrete strategy to do so did not eliminate, reverse, or in any way alter the obtained outcomes. However, when those same instructions orientated attention toward the core parameters of the task, participants spontaneously derived a strategy that allowed them to eliminate their effects (experiment 2). When the participants were provided with a viable response strategy, they successfully reversed the direction of their overall Implicit Relational Assessment Procedure effect (experiment 3). By refining the nature of those instructions, we managed to target and alter individual trial‐type effects in isolation with some success (experiment 4).